What is Carbon Accounting? - Firmansyah, Irman (Accounting and Sustainability, 2024)
This study aims to see the development of research on the topic of "Carbon Accounting" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Carbon Accounting" which comes from the Dimension database with a total of 18956 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Carbon Accounting" research development in the world. The results of the study found that there were 3 clusters with the most used words being carbon emission, emission, carbon, production, factor, change, accounting, effect, and consumption. Then, the topics of research paths related to Carbon Accounting are Carbon accounting in biomass estimation, Carbon accounting in emission reduction strategies, and Carbon accounting in Yellow River Basin development.